KARAKTERISTIK LITOTIPE DAN HUBUNGANNYA TERHADAP CLEAT BATUBARA DI DAERAH KUALA KUAYAN, KOTAWARINGIN TIMUR, KALIMANTAN TENGAH: LITHOTYPE CHARACTERISTICS AND THEIR RELATION TO COAL CLEATS IN KUALA KUAYAN AREA, EAST KOTAWARINGIN, CENTRAL KALIMANTAN - Muhammad Abdurachman Ibrahim; Sigit Arso Wibisono (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2022)
The characteristics of coal can be seen from the lithotype and cleats. This research studied about low rank coal from Dahor Formation to characterize lithotype, cleats, and luster of the coal. Coal lithotypes are associated with maceral in the form of thin bands. Cleats are fractures in coal. Luster is the bright appearance in coal. The coal samples for this research are obtained from Kuala Kuayan area, Kotawaringin Timur, Central Kalimantan. Coal samples were obtained from three exploration wells in this area. Analysis was carried out by looking at the luster and cleats megascopically to the coal seam and to the depth of the coal. The lithotype characteristics indicates that the deeper the depth of the coal seam, the better the bright luster of the coal. The lithotype characteristics are classified as banded coal/clarain. Cleat characteristics from this research are more cleat ferquency and more bright luster. Litotype is quite influential on the frequency of cleats.